„Otwieramy uczniom oczy”. Innowacyjne działania dydaktyczne - Kiwacka, Agata; Letkiewicz-Zamora, Joanna (Paidia i Literatura, 2020)
The article consists of two parts: the first one includes the introduction to art therapy theory, the second one indicates the possibilities of its application in youth education. Agata Kiwacka and Joanna Letkiewicz‑Zamora — with over 20 years of experience in teaching the Polish language, they both work in integration classes in the Middle School No. 1 with Integration Departments in Bytom. They are also special educators in typhlopedagogy and art therapy. They have been using elements of art therapy during Polish classes. They want to expand their work, so they wrote their own programme, which was deployed in the integration classes in the middle school. They share their experiences from the past four years. They are continuously improving, so that the work they have taken on, would continue to give even more to the young people. They help the pupils get to know and accept themselves. They want the pupils to be aware of their worth, open-minded, and creative. So that in the future, they can become “different people.” This change in the young people is happening right in front of their eyes.